Restraining The Privat Logic, Maximizing The Public Logic - Endang Sriwahyuni (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2023)
Analysis of news on BBC.com titled “Covid: Vaccine refusal tackled via Mosque training sessions” is a sign that vaccine refusal from religious community needs tackling involving the opposed community itself to make the program successful. Private ways can be taken into action to tackle covid problem which is considered a public issue. Hence, the meaning or views that see the covid tackling isn’t believed to be collective attempts done by all members of society emerged. The analysis employs the deconstruction theory initiated by Derrida to reveal metaphysical hierarchy in the logic of binary opposition between civilians and community members that are being reversed through the concept of undecidable. The community members’ status becomes higher than civilians bringing impacts to the civilian’s status which is postponed in the concept of differance. The reverse alters covid from a public issue to become a private issue which later emphasizes the concept of dissemination resulting in a pedagogic political education process that has been successful by getting members vaccinated, however, the discourse of Moslem or community members’ identity thickened. Deconstruction is present in both meanings of public and private issues.